Simple carpal ligament release versus release plus epineurotomy in the treatment of carpal tunnel syndromeA comparative study - Hnoosh, Adnan H.; Al-Dulaymi, Thamer. K.; Al-Shydidi, Ali. M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: surgical treatment of established carpal tunnel syndrome (CTS) can be accomplished by various operative modalities, epineurotomy of the median nerve plus carpal ligament release has been advocated by many authors, This study try to evaluate the role of epineurotomy on the outcome of operative treatment of CTS postoperatively, compared to simple release only . Patients and Methods: 48 hands of 42 patients, 34 female and 8 male. where classified in to two groups, one group had a release of the transverse carpal ligament alone, group (1). and the other group had a release plus epineurotomy of the median nerve, group (2). Selection of patients was according to the same clinical criteria regarding physical finding, periods of symptoms preoperatively, as well as sex and age. Positive finding of (EMG) confirming established median nerve dysfunction due to compression, the operative procedure technically unified by the operating team. Clinical assessment of the patients carried out six month post operatively. Results: 60% of group (1) and 56% in group (2) no longer had any symptoms referable to the dysfunction of the median nerve. Physical examination revealed average two–point discrimination of 5.1 mm in group (1) and 4.7 in group (2). The electrophysiological test (EMG) showed average sensory latency of 4.1 mil sec. in both groups. Evaluation of the patients six months postoperatively revealed no detectable significant differences between the two groups with regard to symptoms, objective finding, Tinel’s sign. Phalen test, or (EMG) values. Conclusion: epineurotomy of the median nerve add no benefit to the simple carpal ligament release of the transverse carpal ligament alone. Keywords: Carpal tunnel syndrome. epineurotomy in carpal tunnel syndrome.